2019
DOI: 10.1186/s12917-019-1894-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in thyroid hormones, leptin, ghrelin and, galanin following oral melatonin administration in intact and castrated dogs: a preliminary study

Abstract: Background Melatonin regulates metabolism and metabolism related hormones in mammalians. Castration has some adverse effects on the metabolic hormones of dog. This study was conducted to determine the effects of oral melatonin administration on metabolic hormones, as well as to compare changes of these hormones after administration of melatonin in castrated and intact dogs. Twenty healthy mixed breed mature male dogs were divided randomly into four groups ( n = 5): melat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Their results showed that melatonin increased the level of serotonin but decreased the level of cortisol in intact and castrated dogs [16]. Taheri et al (2019) also studied the effects of melatonin administration on the levels of thyroid hormones, leptin, and ghrelin in intact and castrated male dogs. They observed that melatonin could regulate metabolic hormones and mitigate the metabolic side-effects of castration [18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Their results showed that melatonin increased the level of serotonin but decreased the level of cortisol in intact and castrated dogs [16]. Taheri et al (2019) also studied the effects of melatonin administration on the levels of thyroid hormones, leptin, and ghrelin in intact and castrated male dogs. They observed that melatonin could regulate metabolic hormones and mitigate the metabolic side-effects of castration [18].…”
Section: Discussionmentioning
confidence: 99%
“…Taheri et al (2019) also studied the effects of melatonin administration on the levels of thyroid hormones, leptin, and ghrelin in intact and castrated male dogs. They observed that melatonin could regulate metabolic hormones and mitigate the metabolic side-effects of castration [18]. Furthermore, melatonin has been shown to regulate the activation or inhibition of several transcription factors related to antioxidant response, which can justify the antioxidative effects of this substance [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…36 The serum ghrelin level peaks during the resting phase and is mainly regulated by food intake. 37,38 Some studies have also reported that melatonin also decreases ghrelin levels in dogs and rats, 39,40 while in humans, plasma melatonin concentration correlated negatively with ghrelin, thus suggesting a possible role for melatonin in the regulation of ghrelin concentration. 41 Ghrelin is also a key regulator in glucose homeostasis, and it regulates insulin secretion via heterodimerization of G-protein-coupled receptor GSH-R and somatostatin-5 42 ; this could explain why MT 1 KO females have an increase in plasma insulin after ECD.…”
Section: F I G U R E 4 Environmental Circadian Disruption (Ecd) Inducmentioning
confidence: 99%